Uptake of Pu(IV) by hardened cement paste in the presence of gluconate at high and low ionic strengths - Stietz, J.; Amayri, S.; Häußler, V.; Prieur, D.; Reich, T. (Frontiers in Nuclear Engineering, 2023)
The uptake of Pu(IV) by hardened cement paste (HCP) at degradation state I was investigated in the absence and presence of gluconate (GLU). Furthermore, the influence of the ionic strength was examined by different background electrolytes. For low ionic strength (I=0.3 M) artificial cement pore water (ACW, pH=13) and for high ionic strength (I=2.5 M) cement pore water based on the diluted caprock solution (ACW-VGL, pH=12.5) were used. Sorption experiments were performed under Ar atmosphere using HCP in the binary system HCP / GLU ([GLU]0=1 × 10-1 -1 × 10-8 M) and the ternary system HCP / Pu(IV) / GLU ([ 239 Pu(IV)]0=1 × 10-8 M, [GLU]0=1 × 10-2 M) with solid-to-liquid ratios (S/L) of 0.5 -50 g L -1 within a contact time of 72 h. GLU sorbs strongly on HCP; a saturation of the sorption sites of HCP with GLU was observed at [GLU] ≥ 1 × 10-4 M at S/L=5 g L-1 . The effects of the order of addition of the components Pu(IV) and GLU on the sorption of Pu(IV) on HCP was investigated. In the absence of GLU, a quantitative uptake (S% ≥ 99%) of Pu(IV) by HCP was observed, independent of the ionic strength of the background electrolytes. In the presence of 1 × 10-2 M GLU, the sorption of Pu(IV) on HCP was significantly lower. For X-ray absorption fine structure (XAFS) measurements, powder samples with Pu ([ 239 Pu(III)]0=5 × 10-6 M) sorbed on HCP (S/L=2.5 g L -1 ) were prepared at pH ≈ 13 in ACW and ACW-VGL, respectively. With ACW-VGL as electrolyte, one additional sample was prepared in the presence of GLU ([GLU]0=1 × 10-2 M) for comparison. Pu LIII-edge XANES spectra show that Pu is in the tetravalent oxidation state after uptake by HCP. The structural parameters obtained from EXAFS analysis and comparison with literature indicate incorporation of Pu(IV) into calcium-silicate-hydrate phases of HCP. The different ionic strengths and the presence of GLU had no influence on the near-neighbor environment of Pu in HCP.